Organizing Patient Involvement: An Ethnographic Study - Mette Brehm Johansen (Copenhagen Business School (CBS), 2018)
Patient involvement has become a part of the political agenda in Danish healthcare. Patients are to be involved not only in questions and decisions relating to their own treatment and care – to involve patients in quality improvement has also become a political expectation of quality work in Danish hospitals. During the last 25 years, patient involvement and quality improvement have become connected in Danish healthcare policy. However, the ideal of involving patients in quality improvement is described in very general terms and with only few specific expectations of how it is to be carried out in practice, as I show in the thesis. In the patient involvement literature, the difficulties of getting patient involvement in quality improvement to have in an impact on the planning and development of healthcare services is, for example, ascribed to conceptual vagueness of patient involvement, differences in perspectives, values and understandings between patients and healthcare professionals, or the lack of managerial attention and prioritization.
hdl:10398/9599
Keywords: 650